Global Islamic Calendar Digital Information Mapping - Herlina Nur Afida; Siti Marhamah; Anisah Budiwati (University of Muhammadiyah Sumatera Utara, 2019)
The Global Islamic Calendar doesn't yet exist because it cannot be applied in some Muslim countries in the world. The criteria for Global Islamic Calendar still debated because it’s difficult to apply throughout the world. The development of information technology encouraged astronomers to digitize the site-based global Islamic calendar. Some websites that we have researched have not yet used the integrated calendar criteria set in Turkey Congress 2016. Therefore it is necessary to maping a website that presents a global Islamic calendar so that it can be used as a reference recommendation for Muslim community.